EFFECTIVENESS OF MONTELUKAST SODIUM IN THE TREATMENT OF OBSTRUCTIVE BRONCHITIS IN CHILDREN - Khursankulova Firuza Komilovna,; Ibragimova Marina Fedorovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Introduction. Acute respiratory diseases are the leading cause of childhood morbidity. Obstructive bronchitis is particularly significant, being common among young children, characterized by a complex course, and the risk of complications. Obstructive bronchitis is an inflammatory process in the bronchi, leading to their narrowing and difficulty breathing. Causes may include viral or bacterial agents, allergic reactions, exposure to toxins, and chronic lung diseases.The objective of this study was to improve approaches to the treatment of obstructive bronchitis in the pediatric population.  Materials and Methods. This study involved 48 minor patients undergoing inpatient treatment in the pulmonology department of the Regional Children's Multidisciplinary Hospital and the pediatric department of the Republican Scientific Center for Emergency Medicine. The patients were divided into two groups: the first group included 24 children with obstructive bronchitis who received standard therapy. The second group, also consisting of 24 children, received montelukast sodium in addition to standard therapy.When examining the obtained results and assessing the clinical picture, a comparison of the effectiveness of the improved treatment approach for patients included in the first and second groups would be incomplete without taking into account the specific clinical course of various disease variants.The presented data demonstrate a clear correlation between the severity of preexisting conditions and the severity of the clinical picture. An examination of the table data revealed that, with standard therapy, symptoms of obstructive bronchitis persisted significantly longer in patients in the first group than in the second group, which utilized the modified treatment methods we developed.Conclusion. Including montelukast in combination therapy for children with obstructive bronchitis significantly improves treatment outcomes, making its use imperative. By blocking leukotriene receptors, montelukast helps reduce airway inflammation, reducing bronchospasm and mucosal edema.